"Leadership as a social problem": A conversational engagement with the ideas of Alvin Gouldner. (4th February 2020) - Spector, Bert
Sociologist Alvin W. Gouldner's (1950) book of original and previously published chapters collected under the title Studies in Leadership: Leadership and Democratic Action opens with the proclamation: "Leadership as a Social Problem." Although Gouldner's work is rarely cited in contemporary critical leadership discourse, he and his coauthors make an important contribution to an analysis of the potentially counter-democratic role of leaders. By using an unusual methodology—an imagined conversational engagement between this article's author and Gouldner (who has been dead for 40 years)—the article offers an historical appraisal of the contribution of Studies in Leadership to critical leadership; a contribution that is especially relevant when elected leaders are undermining the institutions and norms that together maintain democratic societies.